Potret Pengetahuan dan Sikap Masyarakat Terhadap Potensi Ketercemaran Air Drainase di Area Pabrik Tahu Kota Palangka Raya - Noor Hujjatusnaini; Ara Aulia Nada; Ayu Novita Ramadhani; Yolanda Wulandari; Hanifah Rahmawati; Nurpah Nurpah; Nursalina Nursalina; Misbah Norrahmah; Astuti Muh. Amin (IAIN Ternate, 2022)
Based on a field survey, the drainage water in the tofu factory area in Jekan Raya District, Palangka Raya is suspected to be polluted. As a form of proof of the assumption, laboratory analysis was carried out. The analysis used is in the form of water quality analysis based on the MPN (Most Probable Number) Coliform which consists of three test stages, namely an estimation test using Lactose Broth (KL) medium, a confirmation test using Brilliant Green Lactose Broth (BGLBB) medium, and a certainty test using Mac Conkey Agar (MCA) medium. This type of research is a direct survey method and laboratory analysis. This research was carried out in October 2021. The results of this study based on the formula and table of MPN values for three tube series obtained with the total MPN Coliform values of 20-2400 cells/100 ml and 247 colonies so that the drainage water quality of the tofu factory area in Jekan Raya District, Palangka Raya in the category of polluted and unfit for consumption.Keywords: Drainage water, Coliform, Most Probable Number, Water quality.